A systematic literature review on the link between peer victimization and literacy during adolescence - Chavers, Ariel L.; Del Tufo, Stephanie N. (Frontiers in Education, 2024)
Peer victimization and literacy failure are on the rise. Yet, there is little understanding of their interplay, particularly during adolescence–a period of heightened sensitivity to social–emotional and academic maladjustment. Guided by the Developmental Cascades Framework, this systematic literature review elucidated how peer victimization and literacy are directly and indirectly linked via negative behaviors, sex, and grade. A total of 21 studies were published between 1993 and 2022 that focused on typically developing 5th- to 8th-graders. Sample sizes ranged from 140 to 86,372 participants. Results indicated a bidirectional connection between increased peer victimization and poorer literacy. Preliminary evidence was found in support of an indirect link via internalizing behaviors, externalizing behaviors, and school engagement, but ambiguous support for the effect of sex. Taken together, adolescents who experience peer victimization are likely to struggle in literacy, as well as exhibit negative behaviors that may only serve to exacerbate this connection.